Peranan Majlis Tafsir Alquran (MTA) Desa Laut Dendang Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Sumatera Utara Dalam Amar Ma’ruf Nahi Munkar - Mourida Nasution, Riski (UIN Sumatera Utara, 2024)
This study aims to find out (1) the concept of amar ma'ruf nahi munkar in Islam (2) the role of the Majlis Tafsir Qur'an (MTA) Representative of Deli Serdang in implementing amar ma'ruf nahi munkar. This research uses a descriptive approach with a qualitative research type. The descriptive approach aims to systematically and accurately describe the facts and characteristics regarding the population or regarding the field. Data collection techniques used are observation, interviews and documentation. The data analysis technique is data reduction, data presentation and drawing conclusions. The data validity technique uses the credibility test, transferability test and confirmability test. The results of the study show that there are many strategies used by the Majlis Tafsir Koran in playing the role of amar ma'ruf nahi munkar. As is done in various activities, for example in the Religious Sector, the Economic Sector, even in the Health Sector. All of these work programs have activities that will be carried out within a year. And every year, all activities carried out are always endeavored to continue to improve their quality. As for the role of the Majlis Tafsir Qur'an (MTA) in implementing amar ma'ruf nahi munkar, namely among the few male and female participants of the MTA Representative of Deli Serdang who have conducted interviews about 'Has MTA succeeded in making the congregation stay away from or leave everything that could cause evil' their answers are almost the same. They said the MTA Deli Serdang Representative with God's permission would make them become better individuals with their recitation activities. The role of the Deli Serdang Representative Council of Tafsir Al-Qur'an in society is enormous. For example in Social Activities such as; blood donors, sending SAR TEAM when there is a disaster, slaughtering sacrificial animals on Eid al-Adha and many more.